Collecting the ashes and scattering it around the household - Mumbai Archive Project Team (Jio Institute, 2024)
After the fire has burned out, the ash is collected and scattered around the household to cleanse it of negative energies. Koli fishermen also apply the ash on their fishing boats and scatter it at sea. They believe this practice ensure the safety of their boats and brings a bountiful catch during the fishing season.